Penggunaan Media Video Pembelajaran Untuk Meningkatkan Hasil Belajar Siswa Pada Mata Pelajaran IPA Siswa Kelas IV SDN Jambewangi Tahun Pelajaran 2020/2021 - Yenni Syamsu S (SOKO GURU: Jurnal Ilmu Pendidikan, 2023)
This study aims to determine the use of video media for learning science subjects and improving science learning outcomes during the pandemic through distance learning for class IV SD Negeri Jambewangi. This research is a class action research conducted in class IV of SD Negeri Jambewangi with 18 students as research subjects. The research includes three cycles. Each cycle includes four stages, namely the planning stage, the action stage, the observation stage, and the reflection stage. The results of the research show that the use of instructional video media can improve the learning achievement of fourth grade students at SD Negeri Jambewangi for the 2020/2021 academic year. After conducting the research, the authors conclude that as a teacher one must know various teaching methods and adjust to current learning conditions so that learning is more varied and students don’t feel bored. To improve science learning outcomes, students must be included in the learning process so as to create independence in solving problems, so that the application of the method of using video learning media is an alternative method.